2018
DOI: 10.1177/0972150918760026
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Relationship between FDI and GDP: A Comparison between India and Its Neighbouring Countries

Abstract: Foreign direct investment (FDI) inflows have been a trigger for accelerating economic growth in a number of countries. The pattern of FDI flows into India and its neighbourhood has been varied and so has been its impact on the economic growth in each of the countries. Although a lot of research has been carried out to establish causality between FDI and economic growth, the results are sometimes varied and conflicting. This study attempted to study the pattern of FDI into the Indian subcontinent and India’s ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
(36 reference statements)
3
16
0
1
Order By: Relevance
“…For example, average annual CO2 emissions in 1998 were 58097.11 kt, which increased to 136,635 kt by 2005. Despite the decline in FDI and fluctuations in GDP growth, CO2 emissions reached approximately 166,300 kt by 2014-2015(Sengupta & Puri, 2020. Many researchers think that an increase in economic development (ED) deteriorates the environmental condition (EC) of a country (Siping, et al, 2019;Aung, Saboori & Rasoulinezhad, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, average annual CO2 emissions in 1998 were 58097.11 kt, which increased to 136,635 kt by 2005. Despite the decline in FDI and fluctuations in GDP growth, CO2 emissions reached approximately 166,300 kt by 2014-2015(Sengupta & Puri, 2020. Many researchers think that an increase in economic development (ED) deteriorates the environmental condition (EC) of a country (Siping, et al, 2019;Aung, Saboori & Rasoulinezhad, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Sothan (2017) applied Autoregressive Distributed Lag Model to find out the relationship between FDI inflows and GDP over the period 1984-2017 in Cambodia, and found that FDI has a crucial eccentric in economic growth, and bilateral relation exists between FDI inflows and GDP respectively. Recently, Sengupta and Puri (2018) have used an OLS regression to scrutinize the influence of FDI Inflows on GDP. They found that FDI inflows have positive impact on economic growth through well-equipped technology and knowledge transfer.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Grafik 11 menunjukkan peningkatan GDP Indonesia dari tahun ke tahun. Bagi negara berkembang, FDI merupakan salah satu motor penggerak pertumbuhan ekonomi penggerak perekonomian (Sengupta & Puri, 2018). Berdasarkan olah data sepanjang tahun 1981-2017 yang nampak di tabel 3, FDI berpengaruh signifikan negatifterhadap GDP ρ value sebesar 0,000.…”
Section: Grafik 8: Fdi Dan Transfer Teknologiunclassified